Influence of Celebrity Endorsement and Product Quality on Buying Interest Trought the Brand Image as an Intervening Variables: Case Study at Kopi Kenangan, Yogyakarta - Prasetia, Rizky Edi; Lukitaningsih, Ambar; Hutami, Lusia Tria Hatmanti (GoAcademica Research & Publishing, 2024)
The main objective of the study is to examine how celebrity endorsement, product quality, and brand image affect consumer’s interest in making purchases. The Research employs a quantitative approach and collects data from 14 individuals who are customer of Kopi Kenangan in Yogyakarta. Sampling method used is non-probability, specifically purposive sampling. Data is gathered by distributing an online questionnaire to the respondents and analyzed using the IBM SPSS application study’s findings can be summarized as follows: Celebrity endorsement (X1) do not have a significant positive impact on consumer’s purchase interest (Y), product quality (X2) has a significant positive influence on consumer’s purchase interest (Y), celebrity endorsement (X1) significantly affect brand image (Z) positively. The brand image variable (Z) Significant influence purchase interest (Y) In a positive way. Furthermore, the research suggest that brand image can act as an intervening variable, mediating the impact of celebrity endorsement and product quality on consumers purchase interest for Kopi Kenangan in Yogyakarta city.